Hysteresis control of the new split-packed-U-cell inverter - Ayoub El Gadari; Hind El Ouardi; Youssef Ounejjar; Kamal Al-haddad (Institute of Advanced Engineering and Science, 2022)
The authors provide a novel hysteresis control method for the SPUC inverter in this paper. The suggested system, which consist of the SPUC inverter and the balancing algorithm can offer eleven levels at output voltage using only seven switches, a closed loop is applied to maintain capacitors voltage at desired values, another hysteresis control that ensures capacitors voltage self-balancing is implemented in open loop which result in the proposed SPUC9 inverter .No voltage sensor or filtering is needed, as a consequence the inverter and installation expenses are kept to a minimum. The authors utilized MATLAB/Simulink environment to simulate the proposed converters. Simulation results prove all the concepts given in this paper. Total harmonic distortion remains reduced and depends on the hysteresis bandwidth